2013
DOI: 10.1148/radiol.13121557
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Planning for Endovascular Aortic Repair of Abdominal Aortic Aneurysms: Feasibility of Nonenhanced MR Angiography versus Contrast-enhanced CT Angiography

Abstract: Measurements obtained with nonenhanced MR angiography appear equally accurate to those of CT angiography in the preoperative planning of abdominal EVAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 18 publications
3
13
2
Order By: Relevance
“…For EVAR election and evaluation of anatomical parameters, CTA remains the standard of reference; however, in the literature, some studies have proposed to run the planning using NC-MRI in relation to the radiation dose saving and preservation of renal function. 6,7 Our study, compared with the other papers published in the literature, 6,7 confirms not only the interobserver agreement of NC-MRI measurements but also their agreement with those provided by CTA: Interobserver ICCs for CTA and NC-MRI showed average values of 0.92 and 0.91 and intermodality ICCs for observer 1 and 2 showed average values of 0.92 and 0.92. We did not observe important differences in lengths, diameters, and angle measurements, except for both external iliac vessel diameters (Tables 1 and 2).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…For EVAR election and evaluation of anatomical parameters, CTA remains the standard of reference; however, in the literature, some studies have proposed to run the planning using NC-MRI in relation to the radiation dose saving and preservation of renal function. 6,7 Our study, compared with the other papers published in the literature, 6,7 confirms not only the interobserver agreement of NC-MRI measurements but also their agreement with those provided by CTA: Interobserver ICCs for CTA and NC-MRI showed average values of 0.92 and 0.91 and intermodality ICCs for observer 1 and 2 showed average values of 0.92 and 0.92. We did not observe important differences in lengths, diameters, and angle measurements, except for both external iliac vessel diameters (Tables 1 and 2).…”
Section: Discussionsupporting
confidence: 83%
“…In the literature, there are few papers about this matter. 6,7 The aim of our study has been to compare NC-MRI to CTA in the planning of EVAR treatments; unlike previous works, 6,7 in this study, we have used 5 different endograft types and employed just 1 software for measurements in NC-MRI and CTA.…”
Section: Introductionmentioning
confidence: 99%
“…Non-contrast MRI is especially useful in patients with poor renal function who may not tolerate iodinated or gadolinium-based contrast agents [21]. Studies have shown good agreement between non-contrast MRI and CTA for AAA diameters, but have used relatively coarse, 2D gradient-recalled echo (GRE) sequences [22]. …”
Section: Discussionmentioning
confidence: 99%
“…We can only speculate on how our findings may translate to different imaging modalities. We would expect our results to closely correlate with APD measurements obtained by CT. 12 Ultrasound measurements of the kidneys are significantly operator dependent. One report suggested that ultrasound systematically underestimated renal length as compared with CT scans.…”
Section: Discussionmentioning
confidence: 99%